Perceptions of libraries and information resources / Qurratui Syaheera Ahmad Termizi - Ahmad Termizi, Qurratui Syaheera (Faculty of Information Management, 2015)
According to Anyira (2011) the most crucial component of the 21st century library is the user. Every effort put into the establishment of a 21st century library is wasted if the library or other information resources is not meant for use. Before we go any further, who is a library user? According to Nwalo (2003), he defined that library user are the people which are as anybody who visit the library with the purpose of exploiting its resources to satisfy their information need. For that, the users and non-users of libraries have their own perceptions towards libraries and any information resources. The perceptions including the library use, awareness and use of library electronic resources, the internet search engine, the library and the librarian, free vs for-fee information and the most important thing is the library" brand itself. All these are common perceptions of libraries and information resources by users and non-users of libraries.